2014
DOI: 10.1136/bcr-2013-201033
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral vocal cord palsy post thyroidectomy: lessons learnt

Abstract: Bilateral vocal cord paralysis is a known possible complication following thyroid surgery. It owes to the close relationship between the recurrent laryngeal nerve and the thyroid gland. The most feared complication of bilateral vocal cord paralysis is airway compromise. We report the case of a 39-year-old woman who underwent total thyroidectomy for multinodular goitre. The surgery was uneventful. However she developed stridor in the recovery bay needing intubation. We postulate that the cause was attributed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…The incidence of recurrent laryngeal nerve palsy after thyroidectomy is in the range of 3.5-6.6%; out of this the incidence of bilateral vocal cord paralysis is as low as 0.58%. 7 A study has shown that 1.3 % of the patients who are scheduled for thyroidectomy can suffer preoperative vocal cord palsy, out of which 76% will have a malignant pathology. 8 Thus, there was a high possibility for recurrent tumour infiltration contributing to vocal cord palsy in this patient.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of recurrent laryngeal nerve palsy after thyroidectomy is in the range of 3.5-6.6%; out of this the incidence of bilateral vocal cord paralysis is as low as 0.58%. 7 A study has shown that 1.3 % of the patients who are scheduled for thyroidectomy can suffer preoperative vocal cord palsy, out of which 76% will have a malignant pathology. 8 Thus, there was a high possibility for recurrent tumour infiltration contributing to vocal cord palsy in this patient.…”
Section: Discussionmentioning
confidence: 99%
“…3 Literature shows that patients with transient vocal cord paralysis may show recovery as early as 3 days to 3 months. 5 This patient in this case was taught proper vocal technique and swallowing manoeuvres with aid of speech therapist. He showed recovery in two months duration with resolved of aspiration symptoms and hoarseness of voice.…”
Section: Discussionmentioning
confidence: 99%
“…BVCPATT was quite rare, with an incidence rate of about 0.80% in this study. Bilateral vocal cord palsy (BVCP) may result from various causes, including endotracheal intubation [7] , laryngeal mask [8] , unidentified causes [9] , use of IONM [10] , and thyroid surgery itself [11] , [12] . In almost half the patients with dyspnea as the main symptom of BVCP, temporary tracheotomy or surgical glottis widening procedures had to be performed [13] .…”
Section: Discussionmentioning
confidence: 99%